Life form, sprout system and season development rythm Potentilla anserina L. (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Potentilla ancerina – vegetative-mobile infant with monopodial-rosette model of sprout. Summer green plants with change: generation of leaves, top bud capacity and stock absorb roots. The rhythm of development coincides with seasonal climate rhythm.
Keywords: life form, season development rythm, Potentilla anserina.